Discrete time analysis of batch processes in material flow systems - Schleyer, Marc (Wissenschaftliche Berichte des Institutes für Fördertechnik und Logistiksysteme der Universität Karlsruhe (TH), 2007)
Scope of this work is the development of appropriate models for the evaluation of batch processes in material flow systems. The presented analytical methods support the long range planning in an early planning stage, in which capacities are determined to minimize the facility costs under the condition of cycle time targets.